1990
DOI: 10.1152/ajpendo.1990.258.5.e864
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin receptors in human placenta: relationship to vascular resistance and thromboxane release

Abstract: This investigation was performed to study the potential role of endothelin in the modulation of fetoplacental vascular resistance in the human placenta. Full-term placentas from uncomplicated pregnancies were studied within 30 min of delivery. The umbilical artery and vein to a single placental cotyledon were cannulated and the artery perfused with RPMI media (0.82 ml/min). Endothelin 1 caused a sustained dose-dependent increase in perfusion pressure. Infused endothelin 1 (50 nM) stimulated thromboxane release… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
29
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 20 publications
4
29
0
Order By: Relevance
“…This is in accordance with studies demonstrating that GTPgS does not inhibit [ 125 I]ET-1 binding to crude membrane fractions of human placenta (10,11). In contrast to other G protein coupled receptors, the binding affinity of ET-Rs is not necessarily reduced by guanine nucleotides.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in accordance with studies demonstrating that GTPgS does not inhibit [ 125 I]ET-1 binding to crude membrane fractions of human placenta (10,11). In contrast to other G protein coupled receptors, the binding affinity of ET-Rs is not necessarily reduced by guanine nucleotides.…”
Section: Discussionsupporting
confidence: 92%
“…In human placenta, ET-Rs were initially identified in crude membrane fractions (9,10). They appear to be most abundant in first-trimester placentas, and their concentration gradually decreases towards term (11).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that GTP-y-S did not inhibit ['25I]-ET-1 binding to membrane preparations of human placenta (Wilkes et al, 1990) or tissues such as porcine cerebellum , whereas an inhibitory effect was demonstrated in human bronchial smooth muscle (Mattoli et al, 1991). It is apparent that the interaction of ET receptors and G-proteins is complex (Sokolovsky, 1991) and variations between tissues may reflect differences in the distribution of ET receptor subtypes and their coupling to distinct G-proteins (Aramori & Nakanishi, 1992).…”
Section: Discussionmentioning
confidence: 94%
“…The precise mediators are not known, however, a number of vasoactive substances have been suggested including the 21 amino acid peptide, endothelin (Howard, 1987;Wilkes et al, 1990). Endothelin (ET) has been shown to be a potent vasoconstrictor of the human isolated foetoplacental cotyledon (Wilkes et al, 1990) and foetoplacental blood vessels (MacLean et al, 1992) and has the potential to influence placental blood flow either directly or in concert with other vasoactive agents including thromboxane A2, prostaglandin F2., prostacyclin, nitric oxide and atrial natriuretic peptide (De Nucci et al, 1988;Hu et al, 1988;Rae et al, 1989;Wilkes et al, 1990;Cameron et al, 1991). Circulating ET levels have been shown to increase during pregnancy and labour (Mastrogiannis et al, 1991); however, conflicting evidence exists concerning the possible role of ET in the pathogenesis of pre-eclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that adrenomedullin might modulate vascular tone as a paracrine regulator, through the inhibition and/or stimulation of vasoactive agents such as nitric oxide (19) and ET-1 (20), produced by feto-placental tissues, which have been demonstrated to regulate placental circulation (21,22). Furthermore both these agents are involved in the control of myometrial contractility (23,24), and a preliminary study has shown that adrenomedullin exerts an inhibitory effect upon the contractile response of rat uterine muscle to galanin (25), suggesting that adrenomedullin, directly through the cAMP or indirectly through the regulation of other modulators, could also affect uterine contractility.…”
Section: Discussionmentioning
confidence: 99%